Identification of peptides with tolerogenic potential in a hydrolysed whey‐based infant formula. Issue 10 (14th August 2018) - Gouw, Joost W.; Jo, Juandy; Meulenbroek, Laura A. P. M.; Heijjer, T. Sam; Kremer, Erica; Sandalova, Elena; Knulst, André C.; Jeurink, Prescilla V.; Garssen, Johan; Rijnierse, Anneke; Knippels, Léon M. J.
Summary: Background: Failure to induce oral tolerance may result in food allergy. Hydrolysed cow's milk‐based infant formulas are recommended in subjects with a high risk of developing allergic disease. Presentation of T cell epitopes is a prerequisite to generate regulatory T cells that could contribute to oral tolerance. Objective: To investigate whether a specific hydrolysed whey‐based infant formula contains peptides that function as T cell epitopes to support the development of oral tolerance to whey. Methods: First, a novel liquid chromatography‐mass spectrometry (LC‐MS) method was developed to characterize β‐lactoglobulin‐derived peptides present in a specific infant formula with a focus on region AA#13‐48 of β‐lactoglobulin, which has previously been described to contain T cell epitopes with tolerogenic potential. Second, the formula was subjected to the ProImmune ProPresent ® antigen presentation assay and MHC class II binding algorithm to identify relevant HLA‐DRB1‐restricted peptides. Third, identified peptides were tested on human cow's milk protein‐specific T cell lines to determine T cell recognition. Results: Thirteen peptides of minimal 9AAs long that overlap with AA#13‐48 of β‐lactoglobulin were identified. Six of them were found across all batches analysed. It was further confirmed that these peptides were processed and presented by human dendritic cells. The identified HLA‐DRB1‐restricted peptides were correlated to AA#11‐30 and AA#23‐39 of β‐lactoglobulin. Importantly, the proliferation assay showed that the synthetic peptides were recognized by cow's milk protein‐specific T cell lines and induced T cell proliferation. Conclusion and Clinical Relevance: This study demonstrates that the tested hydrolysed infant formula contains functional HLA‐DRB1‐restricted T cell epitopes, which can potentially support the development of oral tolerance to whey.